Mind Sound Resonance Technique as an add on yoga therapy to improve quality of life: A narrative Review - Singh, Joychand; K, Archana; Shetty, Anupritha A; Devi, Babbychand Bash; Devi, Geetarani; HM, Prajwal; S, Swathi; TP, Balagovind; Yadav, Amshuman R (Indian Journal of Integrative Medicine, 2024)
Background: Mind sound resonance technique (MSRT), also known as yogic relaxation technique, is a necessary component of yoga that improves physical and functional health. In this article, we provide a thorough summary of the scientific literature on MSRT. Materials & Method: We looked for citations using the keywords "MSRT" and "Quality of life" in PubMed, PubMed Central, and Google Scholar from 2013 to 2023 year. 1875 references in total were found during the search. The review comprised experimental publications, case studies, and case series in English that illustrated the effects of MSRT. Results: Studies indicate that MSRT has positive impact on physiological and therapeutic effects. The MSRT produced positive benefits on the neurocognitive, psychophysiological, cardiovascular, sleep quality, and metabolic functions in healthy people. MSRT is also known to have therapeutic effect. MSRT practiced under supervision of a qualified teacher is generally regarded as safe. Further large-scale investigations with exact designs to comprehend the mechanisms associated with MSRT are justified in light of the beneficial benefits of MSRT. Conclusion: The application of Mind sound resonance technique can potentially enhance quality of life by managing and preventing a number of non-communicable diseases.